Incidence of Non Alcoholic Fatty Liver Disease in Type II Diabetes Mellitus Patients (Medical Forum Monthly, 2024)
Objective: To assess the incidence of non alcoholic fatty liver disease in type II diabetes mellitus patients.Study Design: Prospective / Observational StudyPlace and Duration of Study: This study was conducted at the Department of Medicine, Nishtar Hospital Multan, from April 2017 to December 2017.Materials and Methods: A total no. of 176 took part in the study. Patients were divided into two equal groups on the basis of presence or absence of NAFLD. Age, gender, BMI, plasma AST, plasma ALT, plasma ALP, duration of type II diabetes mellitus, fasting plasma glucose, serum albumin, plasma cholesterol, plasma triglycerides, plasma LDL-C, plasma HDL-C and HbA1c were the variables calculated. All the data was subjected to statistical analysis by using computer software SPSS version 23. Chi square test was applied and P value less than or equal to 0.05 was taken as significant.Results: The mean age, BMI, plasma AST, plasma ALT, plasma ALP, duration of type 2 DM and fasting plasma glucose of non NAFLD patients was 59.15±5.63 years, 32.03±5.32 kg/m2 , 19.68±2.22, 19.87±1.71, 62.32±12.84, 8.40±3.71 years, 124.57±5.66 mg/dl respectively. While, the mean age, BMI, plasma AST, plasma ALT, plasma ALP, duration of type 2 DM and fasting plasma glucose of NAFLD patients was 61.55±8.00 years, 32.05±6.24 kg/m2, 23.03±2.56, 27.28±1.94, 75.19±21.30, 8.12±1.28 years, and 137.45±5.07 mg/dl respectively. The mean albumin (g/dl), plasma cholesterol, plasma triglyceride, plasma LDL-C and plasma HDL-C of non NAFLD patients was 4.20±0.64 g/dl, 150.65±28.44, 114.04±5.99, 87.25±18.16 and 42.97±11.40 respectively. HbA1c was 9.1% (n=8). While, the mean albumin (g/dl), plasma cholesterol, plasma triglyceride, plasma LDL-C and plasma HDL-C of NAFLD patients was 3.80±0.69 g/dl, 158.62±42.02, 150.07±9.03, 87.0±27.89 and 40.76±10.46 respectively. HbA1c was 6.8% (n=6)Conclusion: Conclusion from results of this study can be made that NAFLD has a high incidence in patients with type II diabetes mellitus.